Bank Deleveraging : Causes, Channels, and Consequences for Emerging Market and Developing Countries - Feyen, Erik; Kibuuka, Katie; Ötker-Robe, İnci (World Bank, Washington, DC, 2012)
Just before the 2008-09 global financial crisis, policymakers were concerned about the rapid growth of bank credit, particularly in Europe; now worry centers on a potential global credit crunch led by European banking institutions. Overall, credit conditions across Europe deteriorated markedly in late 2011. Spillover effects are being felt around the globe and imply significant channels through which deleveraging could have disruptive consequences for credit conditions in emerging markets, particularly in emerging Europe. Significant liquidity support provided by the European Central Bank was a "game changer," at least in the short term, as it helped revive markets and limited the risk of disorderly deleveraging. However, the extent, speed, and impact of European bank deleveraging remain highly dependent on the evolution of economic growth and market conditions, which in turn are guided by the ultimate impact of European Central Bank liquidity support, resolution of the sovereign debt crisis within the Euro Area, and the ability of the European rescue fund to provide an effective firewall against contagion.